Reconfiguring Learning Agency: Intelligent Systems and the Posthuman Condition in Virtual Laboratories - Zhang, Ke; Nimno, Ruethai; Thienmongkol, Ratanachote (Journal of Posthumanism, 2025)
Virtual laboratories are increasingly being used to provide immersive and interactive learning experiences. However, their effectiveness depends on incorporating intelligent systems that support adaptive learning, real-time feedback, and enhanced user engagement. This study explores how intelligent systems impact learning efficiency in virtual laboratories by analyzing user experiences, expert evaluations, and system performance metrics. The findings indicate that adaptive learning mechanisms and real-time feedback improve knowledge retention, engagement, and practical application skills. Future research should focus on further refining interactivity, gamification, and system responsiveness to optimize learning outcomes.